Perfil de acidentes de trabalho de uma indústria sucroalcooleira em Minas Gerais - Felícia Emília Camoes Chale (2013)
Objective: To analyze the pattern of illness and accidents of workers in a sugarcane industry in occupational epidemiological features. Method: time series, based on secondary data in the Communications of Occupational Accidents (CAT) at the periods from 2007 to 2011. Results: We analyzed 1746 CAT provided by the alcohol industry analyzed. The average annual rate of occurrence of accidents in the period was 40.7%. The occupational group most affected were the rural workers (67.4%). According to the diagnosis of injury due to accidents, the highest rates were found in the group of Injury, poisoning and consequences of external causes (81.6%) and in the group of diseases of the musculoskeletal system and connective tissue (6.6 %). The profile of the workforce is characterized by men, young, poorly educated, with an average age of 33 years. The company is comprised mostly of rural workers and this was the group that crashed over the period analyzed. Despite the greater number of accidents occur in the agricultural sector, the administrative sector recorded the highest rates of occurrence. Conclusion: In dispite of the work process modernization work accidents are a serious public health problem in brazilian sugarcane industriy and its necessity a efficient intervencion.